Military executives and corporate environmental information disclosure: Evidence from China. (1st January 2021) - Chen, Hongtao; An, Maolin; Wang, Qunwei; Ruan, Wenjuan; Xiang, Erwei
Abstract: This article provides empirical evidence on whether and how executives' military experience affects firms' environmental information disclosure (EID). Using the panel data analysis method based on a sample of 2614 listed Chinese companies from 2007 to 2016, we find that companies with military executives have lower EID than those without military executives. We further divide the executives into chairpersons and CEOs and find that military chairpersons have a significant negative effect on corporate EID, whereas military CEOs have no significant effect on the quality of EID. The results remain robust in a series of robustness tests. Our seemingly against common sense findings suggest that although firms run by executives with the military experience may have a strong environmental performance, the quality of EID of those firms is not necessarily high possibly due to the lack of skills or willingness of military executives in communicating their environmental performance with external stakeholders. Implications of these findings for theory and practice are discussed. Highlights: Effect of executives' military experience on firms' environmental information disclosure (EID) is studied. Companies with military executives have lower EID than those without military executives. Military chairpersons have a significant negative effect on corporate EID. Military CEOs have no significant effect on the quality of EID.